Menelisik Eksistensi Restoran Lake View Kintamani Di Tengah Pandemi Covid-19 - Rosmiati, Kadek Ayu Anjani; Martini, I A Oka; Gorda, A.A Ngr Oka Suryadinatha; Diwya, Ketut Gede Sri (Universitas Pendidikan Ganesha, 2021)
Bali is known for its natural beauty which is a tourist attraction. One of them is Kintamani with views of Mount Batur, Lake Batur and other tourist attractions that make Kintamani visited by many tourists. The number of tourist visits to Kintamani provides opportunities for the surrounding community to open a business. PT Arminusa Wiwayuta also used this opportunity to open a restaurant with the name Lake View Kintamani Restaurant. The restaurant, which was founded in 1972, is still operating well amidst the many competitors and the Covid-19 pandemi. The existence that is still maintained is influenced by several factors, namely natural beauty, menu innovation, friendly service, and has been certified CHSE Standard by the Ministry of Tourism and Creative Economy. With these factors, of course, it cannot be separated from the internal management of human resources, so with this phenomenon the purpose of this study is to find out how the performance of employees in maintaining the existence of the Lake View Kintamani Restaurant in the midst of the Covid-19 pandemi. By using descriptive qualitative methods and data collection techniques through observation, interviews and documentation. Primary data obtained from observations and interviews, while secondary data from previous literature studies such as journals and books. Based on data analysis, the conclusion of this study is that in maintaining the existence of the Lake View Kintamani restaurant in the midst of the Covid-19 pandemi, the quality of human resources is good so as to produce superior performance, in recruiting employees more consider the skills possessed, training and evaluation are ways to develop employee performance and find out the obstacles faced. In maintaining good performance, Lake View Restaurant routinely provides motivation in the form of rewards for employees who excel.